ANALISIS POTENSI PAJAK, TAX GAP DAN COMPILANCE COST SUATU USULAN UNTUK MENGUKUR KINERJA ORGANISASI PAJAK DAERAH - Azhari A Samudrai (FISIPOL UMY, 2015)
Managemenl of road traffict which bad in some large cities in indonesia caused the emergence of vehicle limitation. Although, this idea makes the decline of tax which is received by local govennent. Kompas, gth and gth October 2007, inteNiewed local goverment olficial in jakaia and concluded that goverment had no way out to solve that problem, except immediately goverment realize the plan of vehicle ownership restriction. it is supported by lnstitut Studi Transpottasi ( lnstra ) research which state that in the year of 2014 many cities wi meet traffic problem.